Levantamento do estoque de carbono na vegetação com base em Geotecnologias - Cerqueira, David Brito de (2007)
This study is aimed at estimating the stock of carbon in vegetation, based on the calibration of vegetation index by forest inventory with indirect biomass sampling. To achieve this goal it was defined the territorial dimensions of the vegetation units that compose the area of study through the vegetation mapping. The area of study is located between coordinates UTM 167476 E, 8528819 N 221504 and 8485678 N, zone 24, in the region of Rio de Contas-Ba, and inserted in Biome Caatinga. Through forest inventory, the variability of species in the area was assessed, as well as the determination of the best allometric equations representative of the vegetation. The calibration of the Normalized difference vegetation index (NDVI) was based on the content of C estimated from the application of the allometric equations in geo-referentiated parcels, resulting in an image of carbon content. The quantification of biomass and carbon pool was made from the image of C. The validation was the quantification of carbon in randomly selected plots in the field, using allometric equations and its confrontation with the estimates obtained in the same location by the calibration procedure. Finally, the C gradient was established by crossing the map of vegetation with the NDVI image transformed for different types of vegetation in the areas of study, namely: “caatinga”, “carrasco”, “cerrado” (savannah) and “campo rupestre”. It was concluded that the model proposed in this research to quantify the content of carbon in vegetation (i) showed an average deviation lower than those ones found in standard procedures for inventory of biomass, demonstrating that there was a decrease in the effect of discretization, improving the quality of mapping the carbon content in vegetation, (ii) enabled the quantification of the pool of carbon in vegetation not represented in the vegetation inventory of the area of study (iii) has set the C gradient for different vegetation in the area of study and find the areas where different concentrations of carbon occur within the same category of vegetation,. Additionally, the results showed expanded estimates of the content of C in the “caatinga” vegetation.